Contributions of Recreational Sports Activities to solving some of the psychological problems of Adolescents studying in Educational Institutions. - A comparative study between Adolescent practitioners and non-recreational sports activities- - درار محمد أمين; سلامي سيد علي (sports creativity, 2025)
The current study cam to identify the contributions of recreational sports activities in solving some psychological problems in the male group in adolescence, where the researcher chose among the psychological problems the problem of shyness, and to study this phenomenon the researcher used a sample of 80 adolescent students from secondary education, including 40 adolescents practicing recreational sports activities and 40 adolescents who do not practice recreational sports activities, it was found that there are statistically significant differences between adolescents practicing recreational sports activities compared to non-practicing adolescents and based on the findings of the study recommended the need to be aware of the importance of the actual and regular practice of various recreational sports activities due to the positive return on the health of the adolescent individual and work to provide various sports facilities and work to generalize them to the categories of society The other one.